2020
DOI: 10.3389/fmed.2020.510475
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Deployment of Integrated Healthy Aging Regions Based Upon an Evidence-Based Regional Ecosystem—The Styria Model

Abstract: In 2013, the European Commission founded the platform European Innovation Partnership on Active and Healthy Aging as a communication and innovation network in this domain. The goal of the current study was the development of an integrated regional ecosystem for active and healthy aging for the region of Styria via a step-by-step co-creation process. A mixed model approach was used to establish an ecosystem for active and healthy aging, which includes macro-, meso-and micro-level stakeholders in the province of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Basically, the concept of active and healthy ageing is anything but new for the region, considering that recently a Styrian evidence-based ecosystem for active and healthy ageing was developed, pointing out strong regional capacities in the field concerned [ 12 ]. Borrmann et al demonstrated the need to connect regional stakeholders and develop synergistic initiatives that help to pursue a common strategy for active and healthy ageing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Basically, the concept of active and healthy ageing is anything but new for the region, considering that recently a Styrian evidence-based ecosystem for active and healthy ageing was developed, pointing out strong regional capacities in the field concerned [ 12 ]. Borrmann et al demonstrated the need to connect regional stakeholders and develop synergistic initiatives that help to pursue a common strategy for active and healthy ageing.…”
Section: Discussionmentioning
confidence: 99%
“…Borrmann et al demonstrated the need to connect regional stakeholders and develop synergistic initiatives that help to pursue a common strategy for active and healthy ageing. As a prerequisite, end-user of healthy ageing products and services as well as stakeholders and professionals call for transparent communication and information transfer about processes in this field that directly concern them [ 12 ]. This current publication may be regarded as continuation of the process presented by Borrmann et al, since it picks up the status quo of the Styrian model, tailored towards regional fields of strength within a community-based co-creation process and strategically positions the cross-border region in the field of active and healthy ageing, engaging in the increase of its competitiveness.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Campania Region follows the indications of the WHO "One Health" approach for the implementation of sustainable development goals across all policies, in an inter-sectoral effort (health, environment, education and training, research, and tourism), including different stakeholders along the quadruple helix of innovation (11,12). This innovation ecosystem is based on the approach introduced by the European Innovation Partnership on Active and Healthy Aging (EIP on AHA), a stakeholder-driven, voluntary initiative, launched in 2012 to foster innovation and digital transformation in active and healthy aging across countries and regions within the EU (13)(14)(15).…”
Section: Opportunities From the Internationalization Of The Regional Health Systemsmentioning
confidence: 99%